4x+1=3x-7

Simple and best practice solution for 4x+1=3x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+1=3x-7 equation:


Simplifying
4x + 1 = 3x + -7

Reorder the terms:
1 + 4x = 3x + -7

Reorder the terms:
1 + 4x = -7 + 3x

Solving
1 + 4x = -7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + 4x + -3x = -7 + 3x + -3x

Combine like terms: 4x + -3x = 1x
1 + 1x = -7 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + 1x = -7 + 0
1 + 1x = -7

Add '-1' to each side of the equation.
1 + -1 + 1x = -7 + -1

Combine like terms: 1 + -1 = 0
0 + 1x = -7 + -1
1x = -7 + -1

Combine like terms: -7 + -1 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| (b+c)+7= | | 450-6x=3x | | -2x-7=11-5x | | 9.1=k-3.7+4.1 | | 4(x-8)+x-8+x=26 | | abs(4x+1)=abs(3x-7) | | 5+9/3+4 | | 6(a-3)+10=2(3a-4) | | x+5/2=-9/4 | | 2=-5x+3 | | -3(f-2)=-4(-f+2) | | 36=4q | | -2x+-47=-11 | | 6p-2(3p-4)=16-2p | | -4p^2=-448 | | -14+7k=7(k-2) | | 9-0.5k=9 | | 5x^7-20x^5-3x^2+12= | | -6=t-10 | | -6p-20=-2p+4(1-3p) | | 3-3b=3 | | -11*k=33 | | 4(4h+11)+44h=4(h-17) | | 4x+-15=25 | | 6c^2-17c-14=0 | | 351=-.5x^2+36x-171 | | 7(6-2a)=5(-2+3a) | | 8-(2x-8)=6-3x | | 6(17n+6)=-66 | | 3(3v-2)=14+5v | | 5M+9=3M-5+7 | | 5x+(12x/24)+(8x/16)-80=1460 |

Equations solver categories